Trends and Progress in Human Factors and Organizational Issues in 2016: Learning from Experience - Pelayo, S.; Santos, R.; Section Editors for the IMIA Yearbook Section on Human Factors and Organizational Issues (Yearbook of Medical Informatics, 2017)
Objective: To summarize significant research contributions on human factors and organizational issues in medical informatics published in 2016.Methods: An extensive search using PubMed/Medline and Web of Science® was conducted to identify the scientific contributions published in 2016 that address human factors and organizational issues in medical informatics. The selection process comprised three steps: (i) 15 candidate best papers were first selected by the two section editors, (ii) external reviewers from internationally renowned research teams reviewed each candidate best paper, and (iii) the final selection of five best papers was conducted by the editorial board of the Yearbook.Results: The five selected best papers present studies with rigorous methods, properly designed and described and are, therefore, efficiently reusable for other researches.Conclusion: Human factors and ergonomics- based interventions must be tailored to the context, but meaningful ways must be simultaneously found to generate a stronger evidence base for research and to provide efficient, easy to implement, and useful methods.
Keywords: Human factors; ergonomics; health information technology; usability; organizational issues